Coryphantha macromeris Cell Suspension Cultures: Phytochemical Profiling and Agitation Velocity Effect on Cell Morphology and Viability - E. Cabañas-García; C. Areche; J. Bórquez-Ramírez; R. Muñoz-Miranda; K. M. Rosales-Lopez; E. Pérez-Molphe Balch; Y. A. Gómez-Aguirre; F. Cruz-Sosa (Recent Research Advances in Biology Vol. 8, 2021)
Cell suspension cultures represent an alternative for the production of active plant metabolites. The agitation velocity is one of the main conditions to achieve high cell viability and high yields in metabolite production. In this work, the effect of agitation velocity on cell viability and morphology of Coryphantha macromeris cell suspension cultures was evaluated, and then, the phytochemical profile of two-month-old cells cultivated at 80 rpm was analyzed using Ultra-High-Performance Liquid Chromatography-tandem Mass Spectrometry (UHPLC-PDA-HESI-Orbitrap-MS/MS). The results indicated that the agitation velocity of 120 rpm impacts negatively on cell integrity, while at 80 and 100 rpm, the cells successfully survived and proliferated with similar viability percentages (ca. 97%). The chromatographic and mass spectral analysis indicated the presence of 49 metabolites, and 45 of them were identified. Among the detected compounds, different classes of metabolites such as phenolic acids (gallic acid derivatives), iridoids (gardoside), stilbenes (tyrolobibenzyl E), lignans (acanthoside B), flavonoids (catechin, lantanoside, sakuranin, afrormosin, kaempferol 7-rhamnoside), and phenylethanoids (phlomisethanoside) were found. Our results contribute to the phytochemical knowledge of cacti species and offer the basis for future investigations regarding cell suspension cultures of C. macromeris and related plant species.